(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article examines the role of the mahalla institution in modern society, focusing on its revival and the philosophical foundations of collectivism and solidarity. Historically, the mahalla has served as a unique form of social organization that fosters community cohesion, mutual support, moral values, and shared responsibility among citizens. The study analyzes the socio-philosophical essence of the mahalla, highlighting its contribution to social stability, civic engagement, communal unity, and the preservation of cultural and moral values. It also discusses the modernization processes of the mahalla system, its role in public governance, and its influence on national identity and societal development. The findings provide scientific insights aimed at deepening the understanding of the mahalla as a significant social institution and enhancing its functions in contemporary society.